STUDI KOMPARATIF KURIKULUM MATEMATIKA SEKOLAH DASAR INDONESIA DAN AUSTRALIA - Rilla Gina Gunawan; Eri Rozika; Rusdinal Rusdinal; Nurhizrah Gistituati; Azwar Ananda (JURNAL EDUCATION AND DEVELOPMENT, 2024)
Education policies certainly vary from country to country. To achieve the main goal of education, the Indonesian and Australian governments should work to improve the quality of education in their respective countries by conducting possible curriculum comparisons with other countries. The main objective of this study is to compare the primary school mathematics curriculum in Indonesia and Australia. What are the parallels and differences between the paradigms embedded in the Australian and Indonesian curricula? The research also aimed to find information that would allow a more thorough comparison of the two countries' education systems and mathematics curricula. Mathematics curricula and textbooks from both countries were analyzed for this study, making document analysis the main methodological choice. The research method used was a comparative analysis using qualitative techniques conducted to highlight the similarities and differences between the two. Results show that the Australian mathematics curriculum follows the guidelines set by the National Mathematics Standards Teacher Council of the United States, New Zealand, Finland and the United Kingdom. The topics covered outline the curriculum to be presented to students i.e. Comprehension, fluency, problem solving and reasoning are all addressed as part of the skillset. It is different with Indonesia which is currently using the 2013 curriculum. The 2013 curriculum which is often called Kurtila is a competency-based curriculum. Competency-based curriculum is a curriculum designed to help students learn and practice the skills and knowledge covered in the SKL.